2020
DOI: 10.3390/jcm9092855
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Circulating Plasma miRNA-370 and miRNA-10a from Patients with Hereditary Hemorrhagic Telangiectasia

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant, vascular disorder that presents with telangiectases and arteriovenous malformations. HHT is a genetically heterogeneous disorder, involving mutations in endoglin (ENG; HHT1) and activin receptor-like kinase 1 (ACVRL1/ALK1; HHT2) genes that account for over 85% of all HHT patients. The current diagnosis of HHT patients remains at the clinical level, but many suspected patients do not have a clear HHT diagnosis or do not show pathogenic mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Emerging evidence support the involvement of cellular and EVs miRNAs in cancer progression, diagnosis, and prognosis [56][57][58][59], including melanoma [60][61][62]. Therefore, we investigated the effect of endoglin in the levels of miR-214 and miR-370 as they (i) have been found dysregulated in several cancer types, including skin cancers, (ii) are predicted to target endoglin [64], and (iii) differential expression of circulating miR-370 has been reported in plasma from patients with hereditary hemorrhagic telangiectasia type 1 (HHT1), an autosomal dominant disorder due to mutations in the endoglin gene [64]. We then measured by qRT-PCR hsa-miR-214 and hsa-miR-370 levels in cells and EVs from endoglinexpressing WM-164 cells (Fig.…”
Section: Effect Of Endoglin Expression On Additional Markers Of Melan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence support the involvement of cellular and EVs miRNAs in cancer progression, diagnosis, and prognosis [56][57][58][59], including melanoma [60][61][62]. Therefore, we investigated the effect of endoglin in the levels of miR-214 and miR-370 as they (i) have been found dysregulated in several cancer types, including skin cancers, (ii) are predicted to target endoglin [64], and (iii) differential expression of circulating miR-370 has been reported in plasma from patients with hereditary hemorrhagic telangiectasia type 1 (HHT1), an autosomal dominant disorder due to mutations in the endoglin gene [64]. We then measured by qRT-PCR hsa-miR-214 and hsa-miR-370 levels in cells and EVs from endoglinexpressing WM-164 cells (Fig.…”
Section: Effect Of Endoglin Expression On Additional Markers Of Melan...mentioning
confidence: 99%
“…Some miRNAs are specific for one or more skin cancer type, such as hsa-mir-21 and hsa-mir-221, which are observed in cutaneous melanoma and squamous carcinoma; while hsamir-155 has been detected in melanoma and cutaneous lymphoma. In this work, we have focused our studies on the pleiotropic hsamir-214 and hsa-mir-370, as they are predicted and have been shown to target endoglin [63,64]. Both, hsa-mir-214 and hsa-mir-370 are dysregulated in several other tumors, besides skin cancers, displaying contrasting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported reduced levels of miRs-28-5p and -361-3p in HHT patient peripheral blood mononuclear cells (PBMCs), as well as elevated levels of circulating miR-210 in HHT patients with pulmonary AVMs [24,25]. Various other studies have identified miRNA dysregulation in HHT, but miRNA research in HHT is limited and an exact pathogenic role of any one miRNA has yet to be fully elucidated [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Over 90% of all HHT patients present chronic epistaxis due to nasal telangiectases by the age of 45 years. [ 4 ] Chronic bleeding from gastrointestinal telangiectases develops in at least 20% of patients. [ 4 ] Pulmonary AVM (PAVM) and hepatic AVM have been detected in 24%–40% and 41%–84% of HHT patients, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Chronic bleeding from gastrointestinal telangiectases develops in at least 20% of patients. [ 4 ] Pulmonary AVM (PAVM) and hepatic AVM have been detected in 24%–40% and 41%–84% of HHT patients, respectively. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%